STUDY OF THE USE OF PESTICIDES IN AGRICULTURAL PRODUCTION AND ADVERSE EFFECTS ON NEUROLOGICAL HEALTH IN THE POPULATION RESIDENT IN BRAZIL (CIPEEX, 2026)
he intensive and often inadequate use of pesticides in Brazil has raised increasing concerns regarding their effects on human health, especially in rural areas. Prolonged exposure to pesticides has been associated with various neurological disorders, such as tremors, cognitive deficits, depressive conditions, psychiatric disorders, and even neoplasms. Scientific evidence indicates that the effects are particularly significant in contexts of occupational exposure, affecting more intensely rural workers, pregnant women, and children, who represent particularly vulnerable groups. In this context, it becomes essential to investigate the neurological impacts of pesticide exposure in order to support public health policies and ensure the protection of the most vulnerable groups.The objective was to analyze the relationship between pesticide exposure and its neurological impacts on the Brazilian population. To this end, an exploratory and descriptive study was carried out, based on a literature review of scientific publications from 2014 to 2024. Searches were conducted in databases such as PubMed, BVS, Scopus, and Web of Science, and peer-reviewed studies addressing the neurological effects of pesticides in humans were included.An association was identified between pesticide exposure and neurological manifestations, with organophosphates, pyrethroids, and carbamates being the most frequently cited compounds. The adverse effects included cognitive deficits, headaches, paresthesias, psychiatric, neurodevelopmental, and motor disorders. It is concluded that pesticide exposure causes serious neurological and mental damage, demanding stricter policies, sustainable agricultural practices, and further research on its long-term effects.